The Trade-Offs Cooperative Learning For English Acquisition - Ningsih, Istiqomah Aprimargani Muliayu; Ayu, Luri Dini; Aulia, Halimatul; Maulida, Ema Riska; Jaelani, Selamet Riadi (Faidatuna, 2023)
This study is focused on exploring the strengths and weaknesses of the cooperative learning method in EFL classes according to 2 teachers' and 25 students’ perspectives. The data were collected from interviews, observation, and documentation. The interview data is collected by direct questioning. The findings were categorized into teachers' and students’ perspectives, which state that cooperative learning can facilitate teachers in teaching students effectively and make students able to gain self-confidence and motivation. However, the finding also revealed that cooperative learning is still lacking in managing the abilities of students who are not evenly distributed. The results showed that cooperative learning has both trade-offs in the classroom. Students feel more open to expressing their ideas, making the classroom atmosphere less monotonous and students more enthusiastic about learning. Teachers, on the other hand, feel helped when the material presented requires complicated explanations. Both students and teachers are more comfortable with a variety of methods, considering that cooperative learning has many different strategies that can be implemented by students. On the other hand, students and teachers also feel the problems of the method. It will be discussed further.